Perception of Technological Integrations as a Catalyst for Steam Teacher Education - Jumoke I. Oladele; Mdutshekelwa Ndlovu (Vasyl Stefanyk Precarpathian National University, 2024)
STEAM Education connotes the addition of Arts to STEM education. The fourth industrial revolution as a buildup from the first three revolutions is rapidly changing the education landscape. This study examined students' perception of technology integration for enhancing STEAM teacher training programmes in VUCA times while investigating influencing factors and impending challenges for a holistic assessment. The descriptive survey research design was adopted for this study. The population for the study was students for tertiary institutions while the target population was university teacher trainees offering STEAM-related subjects. The data was collected using a researcher designed and validated questionnaire with an overall Cronbach alpha reliability index of 0.81. The collected data was analysed descriptively (using frequency, percentages, percentile ranking) and inferentially (using a multi-level Factorial ANOVA) tested at 0.05 level of significance. The findings from this study revealed that students had a positive perception of technology integration for enhancing STEAM teacher training programmes. However, the highest-ranking influencing factor for technology integration was the availability of adequate infrastructure while the inadequate access to technology infrastructure was observed as the highest-ranked impediment. The findings of this study informed the conclusion drawn which shows how important technological integration is in pedagogy. As such, teacher training institutions must have the latest resources and use them to advance student growth, including soft skills while upholding STEAM education's emphasis on creativity and innovation as hallmarks of discoveries.